Accuracy of three different fecal calprotectin tests in the diagnosis of inflammatory bowel disease - Jang, Hui Won; Kim, Hyun Sook; Park, Soo Jung; Hong, Sung Pil; Kim, Tae Il; Kim, Won Ho; Cheon, Jae Hee (Intestinal research, 2016)
Several studies have found that the measurement of fecal calprotectin is useful for the early diagnosis of inflammatory bowel disease (IBD). We compared the effectiveness of three different fecal calprotectin kits for initial diagnosis in patients with suspected IBD. We enrolled 31 patients with IBD (18 Crohn's disease [CD], 11 ulcerative colitis [UC], and two intestinal Behçet's disease), five with irritable bowel syndrome (IBS), and five with other colitis (four infectious colitis and one intestinal tuberculosis). Diagnosis was based on clinical, laboratory, and endoscopic examinations. Fecal samples were obtained at the first diagnosis and calprotectin levels were measured using three different kits (Quantum Blue® Calprotectin, EliA™ Calprotectin, and RIDASCREEN® Calprotectin). The overall accuracy for differentiating IBD from IBS or other colitis was 94% and 91%, respectively, for Quantum Blue® (cutoff, 50 µg/g); 92% and 89%, respectively, for EliA™ (cutoff, 50 µg/g); and 82% and 76%, respectively, for RIDASCREEN® (cutoff, 50 µg/g). In patients with CD, the results of Quantum Blue® Calprotectin and EliA™ Calprotectin correlated significantly with levels of the Crohn's disease activity index (Spearman's rank correlation coefficient, r=0.66 and r=0.49, respectively). In patients with UC, the results of EliA™ Calprotectin correlated significantly with the Mayo score (r=0.70). Fecal calprotectin measurement is useful for the identification of IBD. The overall accuracies of the three fecal calprotectin kits are comparable.